Gendered justice? : how women's attempts to cope with, survive, or escape domestic abuse can drive them into crime - Roberts, Jo, Dr (Emerald Publishing Limited, 2022)
Women who encounter the criminal justice system are far more likely to have experienced domestic or sexual abuse than the wider female population. Despite widespread recognition of the link between a woman's victimisation and her involvement in crime, the relationship between the two is still not well understood. Gendered Justice? illustrates how a woman's involvement in crime can manifest as a by-product of her attempts to cope with, survive, or escape domestic abuse. Referencing the first UK-based research of its kind, Roberts explores how a woman's involvement in crime can be explained or contextualised by her experience of domestic abuse. Drawing on the experiences of women serving community-based sentences, all of whom had been subjected to domestic abuse, the author analyses a variety of situations which illustrate how women can become involved in crime when their abuse perpetrator is not present, after the abusive relationship has ended or even years after the abuse has ceased, yet their actions can still be attributed to their victimisation. She also demonstrates how perpetrators of abuse use women's involvement in the criminal justice system as a further weapon of abuse. Built upon the foundations of women's real-life experiences, which have real-world implications, Gendered Justice? introduces a range of recommendations and implications for both policy and practice in the field of criminal justice.
Keywords: Female offenders.; Women -- Crimes against -- Social aspects.; Sex discrimination in criminal justice administration.; Social Science -- Criminology.; Offenders.; elektronické knihy; electronic books